2000
DOI: 10.1590/s0100-879x2000000700007
|View full text |Cite
|
Sign up to set email alerts
|

Expression and biological activity of two recombinant polypeptides related to subunit 1 of the interferon-a receptor

Abstract: Abnormal production of interferon alpha (IFN-=) has been found in certain autoimmune diseases and can be also observed after prolonged therapy with IFN-=. IFN-= can contribute to the pathogenesis of allograft rejection in bone marrow transplants. Therefore, the development of IFN-= inhibitors as a soluble receptor protein may be valuable for the therapeutic control of these diseases. We have expressed two polypeptides encoding amino acids 93-260 (P1) and 261-410 (P2) of the extracellular domain of subunit 1 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Soluble receptor proteins prepared in E. coli (31,48,49) and yeast (50,51), and representing either portions of or the entire extracellular domains of huIFNAR1 (47,49), huIFNAR2 (31,50), and murine IFNAR2 (51), have been studied primarily as potential antagonists of type I IFN action. Nguyen et al (48) reported that the GST-fusion protein of huIFNAR1 extracellular domain inhibited the AV and antiproliferative activities of huIFN-␣1 and competed with the cell surface receptor for binding the IFN.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble receptor proteins prepared in E. coli (31,48,49) and yeast (50,51), and representing either portions of or the entire extracellular domains of huIFNAR1 (47,49), huIFNAR2 (31,50), and murine IFNAR2 (51), have been studied primarily as potential antagonists of type I IFN action. Nguyen et al (48) reported that the GST-fusion protein of huIFNAR1 extracellular domain inhibited the AV and antiproliferative activities of huIFN-␣1 and competed with the cell surface receptor for binding the IFN.…”
Section: Discussionmentioning
confidence: 99%